FOLIAR FERTILIZATION OF BEAN WITH NUTRIENTS, B1 VITAMIN AND METHIONINE - CONTE E CASTRO, Ana Maria; BOARETTO, Antonio Enedi (Scientia Agraria, 2001)
Two experiments were set to determine foliar fertilization effects on bean (Phaseolus vulgaris L.) productivity. The following treatments were used: T1, T2, T3, T4 and T5 (three foliar aplications with formulations 1, 4, 5, 2 and 3 with 3 kg.ha-1 each time), T6 and T7 (three foliar aplications of methionine and vitamin B1, 3 g.ha -1 each time) and T8 (control treatment). T1 consisted of (micro + Mg + S + methionine); T2 (solution with P); T3 (solution with Ca); T4 (micro + Mg + S + vitamin B1), and T5 (micro + Mg + S). Contents of macro and micronutrients of grains, physiological quality of grains and produtivity were evaluated. In a general way, the different treatments, did not influence neither the bean plant produtivity, nor the physiological quality of grain.